2021
DOI: 10.1021/acs.macromol.1c00427
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Dynamics Near the Glass Transition Using Polyelectrolyte Complexes

Abstract: Though the strong transformation in mechanical properties of glass-forming materials such as amorphous polymers near the glass transition, T g, has long been recognized and exploited, efforts to understand and predict this phenomenon at a molecular level continue to this day. Close to T g, where relaxation is considerably slower than predicted by the well-known Arrhenius equation, one of the most versatile and widely used expressions to describe the dynamics or relaxation of glass formers is that of Vogel, Ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…This cooperativity is not reflected in the viscoelasticity until four charges are involved. In a recent mechanism for polymer/polymer coacervates, we concluded that the minimum cooperatively rearranging unit in PEC dynamics was an exchange of two Pol + Pol − pairs with a relaxation rate for PDADMA/PSS of about 10 4 s −1 ( 56 ). A ω b of about 10 5 s −1 in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…This cooperativity is not reflected in the viscoelasticity until four charges are involved. In a recent mechanism for polymer/polymer coacervates, we concluded that the minimum cooperatively rearranging unit in PEC dynamics was an exchange of two Pol + Pol − pairs with a relaxation rate for PDADMA/PSS of about 10 4 s −1 ( 56 ). A ω b of about 10 5 s −1 in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The highest frequency cross-over point is the inverse of the Pol + Pol – pairing lifetime τ min . It indicates the time it takes for a small number of Pol + Pol – pairs to cooperatively rearrange by place exchange. , In the present case, the number of cooperatively relaxing units, n , for 1/τ min = ω of 313 rad s –1 at 45 °C was estimated using data and equations from a recent publication . If T is much greater than T g , the polymer is in the Arrhenius regime for relaxation rate and n = 2 (two Pol + Pol – pairs in PECs) …”
Section: Resultsmentioning
confidence: 99%
“…59,60 In the present case, the number of cooperatively relaxing units, n, for 1/τ min = ω of 313 rad s −1 at 45 °C was estimated using data and equations from a recent publication. 61 If T is much greater than T g , the polymer is in the Arrhenius regime for relaxation rate and n = 2 (two Pol + Pol − pairs in PECs) 59…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Poly­(diallyldimethylammonium chloride) (molar mass, MM, 200 000–250 000 g mol –1 ) was from Sigma-Aldrich and fractionated as described previously to give M w = 70 000, PDADMAC . Two chain lengths of poly­(styrene sulfonate) are denoted as “short chain” (S-PSS) and “long chain” (L-PSS).…”
Section: Methodsmentioning
confidence: 99%
“…Poly(diallyldimethylammonium chloride) (molar mass, MM, 200 000−250 000 g mol −1 ) was from Sigma-Aldrich and fractionated as described previously to give M w = 70 000, PDADMAC. 44 Two chain lengths of poly(styrene sulfonate) are denoted as "short chain" (S-PSS) and "long chain" (L-PSS). Deuterated poly(styrene sulfonate) with M w =104 000, L-dPSS, and M w 14 000, S-dPSS, were matched with protiated poly(styrene sulfonate) (M w 104 000, L-hPSS), made from polystyrene as described by Coughlin et al 45 The level of initial deuteration varied between samples because the polymers were sulfonated with either D 2 SO 4 or H 2 SO 4 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%